2016
DOI: 10.1016/j.jtho.2015.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Germline and Somatic DICER1 Mutations in a Well-Differentiated Fetal Adenocarcinoma of the Lung

Abstract: Germ-line DICER1 mutations predispose to a distinctive tumour predisposition syndrome, the DICER1 syndrome, which is associated with a spectrum of rare mainly childhood-onset tumours. In 2014, a case of well-differentiated fetal adenocarcinoma of the lung (WDFA) was reported in a 16-year-old germ-line DICER1 mutation carrier. Here we report our finding of a characteristic somatic DICER1 RNase IIIb c.5127T>A (p.Asp1709Glu) missense mutation within the WDFA, confirmed using laser capture microscopy. The child ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 5 publications
3
26
0
Order By: Relevance
“…Moreover, few cases of PB were found to harbor somatic DICER1 missense mutation and indicated that DICER1 may be closely related to these tumors presenting later in life. Our results demonstrated that aberrant nuclear expression of β-catenin and missense mutation of CTNNB1 and DICER1 were found only in L-FLAC component but not in both H-FLAC and primitive mesenchymal cells which was further supported by previous studies [17,18].…”
Section: Genetic Sequencing Resultssupporting
confidence: 89%
“…Moreover, few cases of PB were found to harbor somatic DICER1 missense mutation and indicated that DICER1 may be closely related to these tumors presenting later in life. Our results demonstrated that aberrant nuclear expression of β-catenin and missense mutation of CTNNB1 and DICER1 were found only in L-FLAC component but not in both H-FLAC and primitive mesenchymal cells which was further supported by previous studies [17,18].…”
Section: Genetic Sequencing Resultssupporting
confidence: 89%
“…Besides, few cases of PB were found to harbor somatic DICER1 missense mutation and indicated that DICER1 may be closely related to these tumors presenting later in life [24]. Our results demonstrated that aberrant nuclear expression of β-catenin and missense mutation of CTNNB1 and DICER1 were found only in L-FLAC component but not in both H-FLAC and mesenchymal components which was further supported by previous studies [25]. Moreover, our results showed that FAT1 and FAT3 gene missense mutations coexisted in the epithelial and mesenchymal cells in patient 1.…”
Section: Discussionsupporting
confidence: 90%
“…Until recently, neither WDFA nor pulmonary blastoma had been observed in families manifesting DICER1 syndrome [3]. However, in 2015, we identified a second somatic DICER1 RNase IIIb mutation [4] in a WDFA that arose in a 16-year-old germ-line DICER1 mutation carrier [5]. In addition to DICER1 mutations in PPB and WDFA, somatic CTNNB1 mutations (encoding β-catenin) appear to characterise WDFA and pulmonary blastoma [6], and are far less frequent in PPB [7,8].…”
Section: Somatic Dicer1 Mutations In Adult-onset Pulmonary Blastomamentioning
confidence: 75%